CHURCHES IN AFRICA AND THE PROCESS OF SPREADING PENTECOSTALISM. PART 1 - P. . Skirripa (Гуманитарные и юридические исследования)
The article features progressive success of Pentecostal Church in the present time countries of postcolonial Africa. It is due to flexibility and ambivalence of missionary preaching discourses: on the one hand, the prosperity gospel granted by God is claimed, on the other hand, it is argued that the accumulation, competition and private initiative, carried out by unjust methods present absolute evil caused by the devil's instigation, personified by the pagan cults and magic. The recognition of the occult and magic as effective basis allows to construct a new reality, embodied in the religious discourses of the preachers, Pentecostals, and also to assume reasonably, that the options of African modernizations are not reducible to the dominant Anglo-American model.